2012
DOI: 10.1002/anie.201208356
|View full text |Cite
|
Sign up to set email alerts
|

Gold(III) Olefin Complexes

Abstract: Zeise's salt gets company: 185 years after the report of the well‐known platinum(II) ethylene compound, examples of isolable olefin complexes of its isoelectronic neighbor in the periodic table, gold(III), have been prepared (see picture). The complexes are very susceptible towards nucleophilic attack; there is also structural evidence for AuIII–Ag interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
90
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 79 publications
7
90
1
1
Order By: Relevance
“…[5,6] Elucidating the reaction chemistry of gold(III) has provided major challenges and has highlighted that drawing mechanistic analogies between gold(III) and the isolectronic Pd and Pt systems is often not valid. [7][8][9] We show herein that the hitherto elusive Au III alkyne complexes can in fact readily be generated and have Aualkyne bond energies comparable to those of platinum, but are drastically more reactive. [9a] (2; Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Elucidating the reaction chemistry of gold(III) has provided major challenges and has highlighted that drawing mechanistic analogies between gold(III) and the isolectronic Pd and Pt systems is often not valid. [7][8][9] We show herein that the hitherto elusive Au III alkyne complexes can in fact readily be generated and have Aualkyne bond energies comparable to those of platinum, but are drastically more reactive. [9a] (2; Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] However, there are only scarce reports of Au(III)-mediated functionalization of the simplest olefin, ethylene. 9 More recently, Bochmann and co-workers (Scheme 1, bottom) 10 showed that ethylene slowly undergoes a formal insertion into the Au-OAc F bond trans to the pyridine-N in a diarylpyridine CNC pincer complex to yield an Au(III) acetoxyalkyl complex (OAc F = OCOCF 3 ). Reactions of ethylene and propylene with HAuCl 3 and AuCl 3 (tppts) (tppts = 3,3′,3″-phosphanetriyltris-(benzenesulfonic acid) trisodium salt) led to Au(III) hydroxyalkyl species, which upon heating underwent gold reduction to the metal with concomitant formation of organic oxygenated products (alcohols, aldehyde or ketone).…”
Section: Introductionmentioning
confidence: 99%
“…We found recently that C^N^C pincer ligands based on the dianionic 2,6-diphenylpyridine framework are capable of stabilizing a number of novel gold(III) compound types 32,33 , including the first examples of gold(III) hydrides and olefin complexes 34,35 . Given the importance of oxygen ligands in oxidations as well as water cleavage reactions, we decided to explore the reactivity of such gold(III) pincer complexes towards oxygen ligands, including possible Au-O2Au-H interconversions.…”
mentioning
confidence: 99%